Virtual Tour As A Tourist Attraction Promotion Media Using Multimedia Development Life Cycle - Dwi Intan Af’idah (International Conference On Digital Advanced Tourism Management And Technology, 2023)
This study is dedicated to the development of a comprehensive web-based virtual tour application known as the "Virtual Tour Application for Lembah Rembulan Tourist Attraction," designed to function as an information hub. Despite possessing diverse attractions and geographical advantages, the local tourism sector is inadequately promoted due to limited utilization of digital technology. The research follows the Multimedia Development Life Cycle (MDLC) methodology. Notably, the virtual tour website developed in this study provides a website profile, social media information, contact details for the tourist destination operator, and reviews, serving as valuable considerations for prospective tourists. Another noteworthy feature is the dynamic nature of information in the virtual exploration component, enabling tourist attraction operators to make real-time adjustments. It is anticipated that the Virtual Tour Application for Lembah Rembulan Tourist Attraction will serve as a platform for information sharing, fostering immediate community interest in visiting Lembah Rembulan Tourist Attraction. Black-box testing results affirm the effective construction of the system based on proposed scenarios, with two testing roles: visitors and tourist attraction operators.